2013
DOI: 10.1186/1472-6939-14-30
|View full text |Cite
|
Sign up to set email alerts
|

An effective multisource informed consent procedure for research and clinical practice: an observational study of patient understanding and awareness of their roles as research stakeholders in a cancer biobank

Abstract: BackgroundEfforts to improve patients’ understanding of their own medical treatments or research in which they are involved are progressing, especially with regard to informed consent procedures. We aimed to design a multisource informed consent procedure that is easily adaptable to both clinical and research applications, and to evaluate its effectiveness in terms of understanding and awareness, even in less educated patients.MethodsWe designed a multisource informed consent procedure for patients’ enrolment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 36 publications
(49 reference statements)
5
36
1
Order By: Relevance
“…Our findings corroborate international research showing that consent to biobanking has a significant social (intersubjective, familial, communal, and societal) dimension and involves complex trust relationships, which strongly mediate donors’ perceptions of risk and sense of altruism . Many participants felt that biobanking was of such small personal risk and obvious public good that it was a simple decision to make.…”
Section: Discussionsupporting
confidence: 84%
“…Our findings corroborate international research showing that consent to biobanking has a significant social (intersubjective, familial, communal, and societal) dimension and involves complex trust relationships, which strongly mediate donors’ perceptions of risk and sense of altruism . Many participants felt that biobanking was of such small personal risk and obvious public good that it was a simple decision to make.…”
Section: Discussionsupporting
confidence: 84%
“…This trial now demonstrates that patients are also much less aware of important details of the procedure. Comparable to earlier research, we thus found that a combination of verbal and written information leads to better recall than procedures with only verbal or only (short) written information [15][16][17]. In the opt-out procedure, most patients are unaware that their tissue can be used for medical research, that they can control whether their tissue samples will be used, and what the default situation is when they do not act.…”
Section: Doi: 101159/000492662supporting
confidence: 49%
“…To maximize information retention of the informed consent procedure of the 3P initiative, information is provided through multiple sources including: the treating physician, a research nurse or physician assistant, study websites, an online patient movie, brochures, and small executive summary folders. Cervo et al studied a similar multisource informed consent procedure and showed that these patients retain much more information (!95% of the questions about the informed consent answered correctly) [28] compared to 56-88% without the provision of multisource information [27].…”
Section: Discussionmentioning
confidence: 99%